The development of family planning (KB) program in Kulon Progo, Indonesia (1971-1998) - Pramadani, Sarah; Sa'diah, Halimatu; Alifi Nur Prasetia Nugroho; Nurul Huda (Harmoni Sosial: Jurnal Pendidikan IPS, 2024)
Kulon Progo Districts had been participated in the realization of KB program in Indonesia. The purpose of this research is to investigate: 1) General condition of Kulon Progo Regency before 1971; 2) The implementation of Family Planning program (KB) in Kulonprogo district from 1971 to 1998; 3) the socio-economic and cultural impact of the realization of family planning (KB) program in Kulonprogo district from 1971 to 1998. This research used historical research method according to Kuntowijoyo which consist of: (1) Topic selection; (2) Heuristics; (3) Source Criticism (Verification); (4) Interpretation; (5) Historiography. The result of this research shows that (1) General condition in Kulonprogo district before 1971 is an underdeveloped area and lack of welfare. (2) The realization of KB program in Kulonprogo district includes finding new acceptors, increasing the number of active acceptors (KB Lestari) and operational activities which consist of Communication, Education and Information (KIE), Contraception service and integration with other government agencies. (3) The realization of family planning (KB) program in Kulon Progo district from 1971 to 1998 result in socio-economic and cultural impact.